Inovasi Desain dalam Menjaga Eksistensi Bangunan Cagar Budaya : (Kasus: Rumah Tinggal di JL. Wastukencana Bandung) - Dewi, Adelita Arifani Fitria; Utami; Nadia Silvianingsih; Raisya Salsabila Fasha (RUAS, 2024)
The continued existence of colonial buildings in Indonesia represents a process of design adaptation. Colonial buildings have experienced numerous functional changes, necessitating new design modifications within existing structures, all while preserving their cultural heritage. This necessitates a transformational and innovative design process. This study aims to identify the design innovations of neoclassical-style colonial buildings in Wastukencana, Bandung, from their establishment until they transitioned into a commercial function. We used an exploratory description of existing residential buildings in the Netherlands and Wastukencana in 1819, before they transitioned into commercial functions. For a period of more than 100 years, the residential building has been able to survive as a comfortable place to live without change. The transformation of the building into a commercial facility necessitates new adjustments while maintaining the integrity of the existing structure. The Netherlands carried out design innovations at the beginning of its establishment, transforming the shape of the roof, the façade, and using materials suitable for the tropical climate. Meanwhile, the main structure transitions from residential to commercial use by incorporating separate building elements, preserving its cultural heritage status.